Data files for ‘Breeding habitat selection of urban peregrine falcons (Falco peregrinus) in London’ - Mak, Brandon; Francis, Robert; Chadwick, Michael; Greenspace Information for Greater London (GiGL) CIC (King's College London, 2021)
Understanding habitat selection by individual animals within their home range is crucial to facilitating their conservation. Peregrine falcon (Falco peregrinus) populations are increasingly urbanised, but little is known about their urban habitat use. Thus, we analysed the breeding habitat selection and nest spacing of peregrine falcons in London, United Kingdom, based on nest site locations identified through records of public sightings submitted to an online database between 2003-2018.
Keywords: Bird Diversity; Urban Peregrine Falcon; Public Sighting; Habitat Preference; Compositional Analysis; Avifauna